2023
DOI: 10.1021/acs.jafc.2c07702
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Effects and Molecular Mechanisms of Tea and Its Active Compounds on Nonalcoholic Fatty Liver Disease

Abstract: Nonalcoholic fatty liver disease (NAFLD), the most common chronic liver disease, is a multifactorial disease resulting from the interaction between environment, genetic background, and metabolic stress. Most treatments for NAFLD include dietary intervention and exercise show limited efficacy due to the complex mechanisms involved in NAFLD. Meanwhile, drug therapy is accompanied by serious side effects. The development of high-efficiency natural supplements is a sustainable strategy for the prevention and treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 202 publications
0
7
0
Order By: Relevance
“…Various types of tea differ in sensory characteristics, such as appearance, aroma, taste, and brewing color. Meanwhile, the production and consumption of tea has been flourishing as evidence mounts that tea has multiple health benefits. …”
Section: Introductionmentioning
confidence: 99%
“…Various types of tea differ in sensory characteristics, such as appearance, aroma, taste, and brewing color. Meanwhile, the production and consumption of tea has been flourishing as evidence mounts that tea has multiple health benefits. …”
Section: Introductionmentioning
confidence: 99%
“…There are a variety of healthy bioactive substances in tea; for instance, tea polyphenols have good effects on regulating lipid metabolism (Yan et al., 2020), and theanine can mediate the apoptosis of tumor cells and inhibit tumor growth and metastasis, which can also improve brain function and enhance memory (Wang, Zheng, et al., 2021; Wang, Gao, et al., 2021). Long‐term regular tea drinking can prevent a variety of metabolic disorders and neurodegenerative diseases (Huang et al., 2022; Lin, Wei, et al., 2021; Lin, Sun, et al., 2021; Prasanth et al., 2019; Shao et al., 2022; Xing et al., 2019; Xu et al., 2022, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…and metastasis, which can also improve brain function and enhance memory (Wang, Zheng, et al, 2021;. Long-term regular tea drinking can prevent a variety of metabolic disorders and neurodegenerative diseases (Huang et al, 2022;Lin, Wei, et al, 2021;Lin, Sun, et al, 2021;Prasanth et al, 2019;Shao et al, 2022;Xing et al, 2019;Xu et al, 2022Xu et al, , 2023.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of IBD in Asia is far lower than that in Western countries; the high sugar and fat of Western diet were prone to promote the occurrence and development of IBD in Western countries, whereas habitual tea drinking in Asia might exert a protective effect on IBD. , Tea is the secondary largest beverage after water due to its pleasant flavor and multiple health benefits. Several studies have reported the effective alleviative effects of tea on IBD. Huang et al found that ripened Pu-erh tea could effectively decrease the disease activity index (DAI) and inhibit the secretion of proinflammatory cytokines via downregulating the expression of hypoxia inducible factor-1α (HIF-1α) and suppressing the activation of the nuclear factor kappa-B (NF-κB) pathway to protect the colon .…”
Section: Introductionmentioning
confidence: 99%